Pembelajaran Berbasis Komputer Model Tutorial di Sekolah Dasar - Utomo, Jepri; Purwaningsih, Purwaningsih (Pengembangan Pendidikan dan Pembelajaran Sekolah Dasar, 2022)
This study aims to determine the computer-based learning tutorial model at SD Negeri 3 Tolitoli. This research uses a qualitative research type; where in collecting data using observation techniques, interviews, and documentation. The data analysis technique used is data reduction, data presentation, conclusion drawing and verification. The results showed that the tutorial model computer-based learning analysis at SD Negeri 3 Tolitoli was carried out well through 8 indicators, namely: distinguishing basic competencies on materials that contain competency demands, determining the selection of peer tutorials, having students who are already capable, compiling learning observation instruments for tutorials. , group students by including intelligent students who become tutors, make observations on learning, provide clarification, and draw conclusions from peer tutorial results